Implications of Moral Education on Children's Character in the Digital Era: Insights from Surah Al-Isra, Verses 23-24 - Rochmat, Cecep Sobar; Alamin, Nurul Salis; Amanah, Khusnul; Kamal, Shofiya Taqiya; Azani, Mohammad Zakki; Wibawa, Bagus Asri (Qualitative and Quantitative Research Center, 2024)
In the digital era, the moral education of children's character presents novel difficulties and opportunities for schools, parents, and society. Young children are readily exposed to a wide range of material and interactions that were previously unheard of. Moral is an awareness that helps children through all kinds of skills and life values that contribute to social life, where moral education cannot be separated from character education. This study aims to determine the meaning and implications of moral education for children's character in the Al-Qur'an, Surah Al-Isra verses 23-24. The method used in research is library research with a methodological approach to the interpretation of the Al-Qur'an, the methodology is a method using the process of searching for the interpretation of the Al-Qur'an and collecting interpretations of verses related to moral implications on children's character. Research on Tafsir Al-Qur'an is included in the type of literature study research. Based on the research results, the values contained in Surah Al-Isra verses 23-24 command us to recognize Allah SWT and respect both parents. This verse also explains the importance of parents in teaching moral values that will make a child have charity. As a suggestion to the reader that this verse emphasizes the importance of filial piety to parents and the urgency of moral education for children. This research contribution provides information about the religious approach in the era of digital education, which is constructive in cultivating moral education for children's character.